2018
DOI: 10.1371/journal.pone.0195259
|View full text |Cite
|
Sign up to set email alerts
|

Dominant serotype distribution and antimicrobial resistance profile of Shigella spp. in Xinjiang, China

Abstract: Shigella represents one of the major diarrhea-inducing pathogens threatening public health, but its prevalence and antimicrobial resistance profile in Xinjiang Uygur Autonomous region, China, remains unclear. We conducted comprehensive investigation of Shigella serotype distribution and antimicrobial resistance pattern in Xinjiang, identifying 458 Shigella isolates between 2008 to 2014. Shigella flexneri was identified as predominant species, and several S. flexneri serotypes were isolated, including atypical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 59 publications
(57 reference statements)
3
11
0
Order By: Relevance
“…Further, serotype 6 was the most dominant. Heterogeneity in distribution of other serotypes was noticed among isolates in this study as has been elaborated in Additional file 2: Table S3 [5,10, 2629]. The mixture of other serotypes identified in this study is disparate, thus showing that there is no homogenous distribution of serotypes globally as shown in Table 2.…”
Section: Discussionmentioning
confidence: 76%
“…Further, serotype 6 was the most dominant. Heterogeneity in distribution of other serotypes was noticed among isolates in this study as has been elaborated in Additional file 2: Table S3 [5,10, 2629]. The mixture of other serotypes identified in this study is disparate, thus showing that there is no homogenous distribution of serotypes globally as shown in Table 2.…”
Section: Discussionmentioning
confidence: 76%
“…Similar trends have earlier been noted in Iran [ 36 ] and Ethiopia [ 37 ], where they reported 49.8% and 14.0%, respectively, of Shigella flexneri isolates. However, in a study conducted in Xinjiang, Uygur in China, although Shigella flexneri was the most prevalent species (79%), other species like Shigella sonnei were also reported [ 38 ]. The differences in species recorded in different studies is attributed to the geographical stratification of Shigella species due to countriess’ economic statuses.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular characterization of S. flexneri isolates is important to understand the disease burden caused by new Shigella serotypes, vaccine development and to prevent the emergence of MDR bacteria. [7][8][9][10][11][12][13]20,21 Several studies reported evidence about association of S. flexneri serotype with antibiotic resistance pattern. [4][5][6][7][8][9][10][11][12][13][14] The current study is highlighting the molecular serotyping of S. flexneri and their association with antimicrobial resistance patterns in Pakistan.…”
Section: Discussionmentioning
confidence: 99%